(untitled) (Asian Journal of Medical and Biological Research, 2015)
An experiment was conducted in randomized complete block design (RCBD) with three replications in the experimental field of Regional Horticulture Research Station (RHRS), Bangladesh Agriculture Research Institute (BARI), Lebukhali, Patuakhali during April, 2014 to October, 2014 for assessing the inbreeding depression, genetic parameters, gene action and segregation pattern of Okra [Abelmoschusesculentus (L.) Moench]. The experiment was comprised of five commercial hybrid Okra genotypes such as Tara sonali, Bimala, Juboraj, Suvo 1and Noor, their respective F2 progenies along with a check variety named as BARI Dherosh 1. Results of the experiment indicated that there were considerable variability among the F1 and their F2. The yield were in-between 14.81 to 7.92 Kg plot-1in case of F1 generation, which deteriorate to 10.32 to 5.32 Kg plot-1 in F2 generation. Broad sense heritability computed through variance component method showed that all the quantitative traits were moderate to highly heritable. The trait yield per plot exhibited 68.83% broad sense heritability coupled with 50.96% genetic advance suggesting the existence of sufficient amount of genetic variability for improvement of this trait and also indicates that the trait is more amenable to selection and could be improved easily. In case of segregation pattern, plant height and pod pubescence content exhibit as polygenic trait. Leaf shape, fruit base shape and branching pattern showed complete dominance and fruit color displayed incomplete dominance. The present investigation thus provide information about the nature and magnitude of genetic variation, segregation pattern and inbreeding depression for yield and its components in okra so as to formulate suitable breeding strategy and isolate potential parents and promising crosses for further breeding program. Asian J. Med. Biol. Res. June 2015, 1(2): 316-335